Biofilm Inhibition of Spoilage Bacteria by Argentinean Fruit Juices with Antihypertensive Activity - Vallejo, Claudia Veronica (2013)
Argentinean juices have been studied for their antihypertensive activity, the inhibition of bacteria biofilm formation and the effect on the viability of wine yeast. The influence of phenolic compounds on these activities was evaluated. These studies are the first step for the development of a new type of wine that includes grape must supplement with fruit juices with antihypertensive effect. All juices posses a high antihypertensive activity, higher than 50%. Strawberry juices and eureka lemon showed the highest activity, whereas clarified juices posses the lowest activity. All studied juices produce a high inhibition of bacteria biofilm formation, and the strawberry, orange and mandarin varieties not affect the growth or viability of yeast. Our results permit to conclude that it could be possible the use of these juices in a new type of wine or as a source of new antihypertensive agents for pharmaceutical industry.